The Costs of Power Outages: a Case Study from Cyprus - Poullikkas, Andreas; Zachariadis, Theodoros (My University, 2012)
We study the costs of electricity disruptions in Cyprus, which suffered severe power shortages in summer 2011 after an explosion that destroyed 60% of its power generating capacity. We employ both economic and engineering approaches to assess these costs. Among other calculations, we provide estimates of the value of lost load by economic sector and the hourly value of electricity by season and type of day. The results of two economic methods employed to assess welfare losses differ largely, indicating that the assessment of outage costs is associated with many uncertainties. Our calculations show that the emergency actions taken by national energy authorities in response to that accident, though not necessarily optimal, have generally been appropriate and in line with international best practices: the additional costs incurred due to these measures are lower than the economic losses avoided thanks to these actions. Preferential treatment of specific consumer types in the case of repeated power outages remains an open policy question.
Keywords: Electric power failures; Energy; Cyprus; Cost accounting; Energy crisis; Welfare losses; Value of lost load